2007
DOI: 10.1111/j.1365-3164.2007.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia spp. overgrowth in allergic cats

Abstract: A series of 18 allergic cats with multifocal Malassezia spp. overgrowth is reported: atopic dermatitis was diagnosed in 16, an adverse food reaction in another and one was euthanized 2 months after diagnosis of Malassezia overgrowth. All the cats were otherwise healthy and those tested (16 out of 18) for feline leukaemia or feline immunodeficiency virus infections were all negative. At dermatological examination, multifocal alopecia, erythema, crusting and greasy adherent brownish scales were variably distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
1
39
2
1
Order By: Relevance
“…However, a recent study investigating feline SBP revealed that almost 50% of cases were associated with underlying AD, correlating with the findings of the present study. To a lesser extent, some cats with AD in this study had secondary Malassezia dermatitis (7%), which has also been identified previously in a cohort of healthy cats with allergic dermatitis, despite earlier suggestions of internal disease associations in cats . Of note, less than one‐third of cats with AD complicated by SBP in the present study had a reported ‘good’ response to systemic antimicrobial therapy, and severe pruritus and persistent self‐trauma were recognized as problematic for early case management in this group.…”
Section: Discussionsupporting
confidence: 53%
“…However, a recent study investigating feline SBP revealed that almost 50% of cases were associated with underlying AD, correlating with the findings of the present study. To a lesser extent, some cats with AD in this study had secondary Malassezia dermatitis (7%), which has also been identified previously in a cohort of healthy cats with allergic dermatitis, despite earlier suggestions of internal disease associations in cats . Of note, less than one‐third of cats with AD complicated by SBP in the present study had a reported ‘good’ response to systemic antimicrobial therapy, and severe pruritus and persistent self‐trauma were recognized as problematic for early case management in this group.…”
Section: Discussionsupporting
confidence: 53%
“…9,20 In the present case, the Malassezia infection was located on the alopecic shoulder and back, which are not typical locations for Malassezia dermatitis based on the previous reports. Since Malassezia usually establishes infection in immunologically impaired skin (such as that affected by atopic dermatitis, allergic dermatitis, or sebaceous adenitis 6,13 ), the altered epidermal condition resulting from AA is likely a contributing factor for Malassezia infection in the present case.…”
Section: Discussionmentioning
confidence: 95%
“…Hygiene practices and environmental exposures are thought to contribute to the differences in diversity and taxa between host species, although studies are still required to better investigate their influence on the microbiome. The microbial communities present on feline skin have only been investigated using culture dependent methods . The results of these studies are variable and fungal genera commonly isolated include Penicillium , Cladosporium , Aspergillus , Alternaria and Malassezia .…”
Section: Introductionmentioning
confidence: 99%